1980
DOI: 10.1029/wr016i002p00289
|View full text |Cite
|
Sign up to set email alerts
|

On the statistical characteristics of drought events

Abstract: Several statistical tests are performed on streamflow series for purposes of analyzing multiyear drought events. These statistical tests on both high-flow and drought event parameters include (1) stationarity in terms of their linear trend; (2) randomness in terms of lag-1 serial correlation; (3) correlation and cross correlation between these parameters (duration, magnitude and severity). The test results and their implications are discussed in relation with the characterization of high-flow and drought event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
1
15

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(142 citation statements)
references
References 8 publications
(3 reference statements)
2
124
1
15
Order By: Relevance
“…For crop production, drought impact depends on three main characteristics being severity, length and timing of drought (Dracup et al 1980). These characteristics are incorporated into the delineation of CIMMYT mega-environments underlying their drought resistance breeding programmes.…”
Section: Climate Subsystemmentioning
confidence: 99%
“…For crop production, drought impact depends on three main characteristics being severity, length and timing of drought (Dracup et al 1980). These characteristics are incorporated into the delineation of CIMMYT mega-environments underlying their drought resistance breeding programmes.…”
Section: Climate Subsystemmentioning
confidence: 99%
“…A significant amount of research (Gupta and Duckstein, 1975;Sen, 1980;Dracup et al, 1980;Zelenhastic and Salvai, 1987;Frick et al, 1990;Kendall and Dracup, 1992;Loáiciga and Leipnik, 1996;Chung and Salas, 2000;Cancelliere and Salas, 2004) has developed probabilistic methods to investigate properties of droughts. Multiple attributes of droughts have been evaluated in these studies, but significant correlation relationships are not revealed by separate consideration of correlated characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold is assumed to be equal to a given percentile of the flow-duration curve (generally, the 95-, 90-, 80-, 70-, or 60-percentile). Among others, see Sen [1977]; Dracup et al [1980b]; and Clausen and Pearson [1995] for the application of the run method at a yearly time scale, and Zelenhasić and Salvai [1987] ; Tallaksen et al [1997] ; Demuth and K€ ulls [1997]; Demuth and Heinrich [1997]; Kjeldsen et al [2000]; Engeland et al [2004]; Byzedi and Saghafian [2009] ;and Byzedi [2010] at a daily time scale.…”
Section: Introductionmentioning
confidence: 99%